Dental health of preschool children after two-years of a supervised tooth brushing program in Southern Israel - Lena Natapov; Dan Dekel; Vadim Pikovsky; Shlomo Paul Zusman (BMC, 2021)
Abstract Background Supervised tooth brushing is an important part of leading national oral health improvement programs in different countries. With the cessation of water fluoridation in 2014, a new program was immediately required to provide community-based caries prevention, especially amongst young children. The aim of this study was to determine whether a supervised tooth brushing program (STBP) in kindergartens could reduce dental caries amongst preschool children, when compared with children from the same community who did not participate in the program. The study was performed 2 years after the start of the program. Methods Two Jewish and two Arab local authorities (one participating and one control) were randomly chosen. In each local authority, 4 kindergartens (children aged 5) were randomly chosen, giving a total of 16 kindergartens. Children in the intervention group brushed once daily at kindergartens, with fluoridated toothpaste, for two school- years. All the children were examined using the WHO Oral Health Survey Methods Ed.4. Results Two hundred eighty-three five-year-old children were examined, 157 of them Jewish (86 participants in STBP, 71 non-participants) and 126 Arab (59 vs 67 respectively). Among Jewish children, the fraction of untreated decayed teeth was 61% in the participant group and 65% for non-participants, and amongst the Arab children 69% vs. 90% respectively. The fraction of treated decayed teeth for the participant group was 37% compared to 29% for the non-participants among Jewish children, whilst for the Bedouin group it was 23% vs. 8% respectively. Conclusions After 2 years, supervised tooth brushing with fluoride toothpaste shows a favorable effect. This study suggests that dental health of children participating in STBP was better than the control group. Fewer carious teeth and more treated carious lesions were recorded in this group. This program can be applied to low SES communities nationwide. Guidelines for fluoride concentration in toothpaste for children should be re-considered based on high caries levels.